Lactating Canadian Women Consuming 1000 µg Folic Acid Daily Have High Circulating Serum Folic Acid Above a Threshold Concentration of Serum Total Folate. Issue 7 (13th June 2018) - Stamm, Rosemary A; March, Kaitlin M; Karakochuk, Crystal D; Gray, Andrew R; Brown, Rachel C; Green, Tim J; Houghton, Lisa A
Abstract: Background: Consumption of high-dose folic acid supplements is common throughout pregnancy and lactation in several countries, including Canada, Brazil, and the United States, and may lead to high levels of circulating unmetabolized folic acid. Objective: The objective of the study was to characterize serum and whole-blood folate forms in Canadian lactating women regularly consuming a daily high-dose folic acid supplement. Methods: One-hundred and seventeen Canadian lactating women aged between 18 and 42 y, with a geometric mean ± SD prepregnancy body mass index (kg/m 2 ) of 23.1 ± 1.2, were enrolled in a vitamin D supplementation trial between 13 and 22 wk of gestation. As part of the trial, the women received a daily multivitamin containing 1000 µg folic acid throughout pregnancy and lactation until 8 wk postpartum. At 8 wk postpartum, serum folate forms, including folic acid and RBC total folate, were determined from nonfasted blood samples. Differences in median folate vitamer concentrations among quintiles of serum total folate status were assessed by the Wald test and quantile regression methods. A breakpoint in the relation between serum folic acid and serum total folate was modeled with the use of the segmented package in R. Results: Median serum total folate concentration among participants was 79.3 nmol/L (5th–95th percentile 30.7–186 nmol/L) and median RBC folate concentration was 2790 nmol/L (5th–95th percentile 1330–4850 nmol/L). There was a breakpoint in the relation between serum total folate and serum folic acid at 78.5 nmol/L (95% CI: 67.9, 89.1 nmol/L), below which serum folic acid was not associated with serum total folate, and above which serum folic acid increased 0.78 nmol/L (95% CI: 0.70, 0.86 nmol/L; P < 0.001) for each 1 nmol/L increase in serum total folate. Conclusions: These data demonstrate the potential for high serum folic acid concentrations proportional to overall folate concentrations in lactating women with serum total folate >80 nmol/L taking high-dose supplemental folic acid. This study was registered at clinicaltrials.gov as NCT01112891.